Legality and legitimacy of elections in the constitutional-legal dimension - Vasilevich, Grigory A. (Journal of the Belarusian State University. Law, 2023)
The author of article analyses the concepts of legality, legitimacy and constitutionality. In doctrine and in practice, the concepts of legality and legitimacy are interpreted differently. The position on the concept of legitimacy is substantiated in the article. It implies not only a purely legal assessment, but also such an important evaluation criterion as the attitude to any political institution or to the state power of the population, so, an important factor is public opinion. On the basis of analysis of the constitutional legislation, including the Electoral Code of the Republic of Belarus, a number of conclusions were made. The practice will allow to answer the question about how many violations of the electoral legislation can raise the question of legitimacy verification. There is some competition between the Constitutional Court of the Republic of Belarus verification of constitutionality of elections and consideration of the issue of legitimacy by the All-Belarusian People’s Assembly. Purely hypothetically we can imagine a situation when one of the subjects addressed the question about the legitimacy of elections to the Constitutional Court of the Republic of Belarus and another one to the All-Belarusian People’s Assembly. It has been suggested that the scope of powers of the All-Belarusian People’s Assembly could be expanded. The All-Belarusian People’s Assembly should have the right to consider, upon the proposal of the subjects specified in the Electoral Code of the Republic of Belarus, the legitimacy of elections in any term of the deputies of the corresponding convocation. The All-Belarusian People’s Assembly should also have the right to check the legitimacy of elections to local councils of deputies in accordance with clause 7 of art. 893 of the Constitution of the Republic of Belarus at the level of the Electoral Code of the Republic of Belarus and the Law of the Republic of Belarus of 7 February 2023 No. 248-З «On All-Belarusian People’s Assembly».